COMPUTATIONAL STUDY OF METHODS FOR FLUID STRUCTURE INTERACTION (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This work presents the numerical simulations of problems of solid and fluid mechanics aiming a future fluid structure interaction, considering an immersed flexible beam. In recent years, a number of applications dedicated to flow-induced vibrations have been proposed in order to satisfy the increasing demand for high performance and safe operation of mechanical systems. The vibration response of aircraft wings, bridges, buildings, and engine blades, are frequently obtained by using fluid-structure interaction approaches. Therefore, the flow-induced vibrations are determined from the mathematical models of both the fluid and the submerged structure. A cantilever beam is used to demonstrate the efficiency of the proposed methods for the integrated solution of these domains. A finite element model based on the Euler-Bernoulli theory is used to obtain the dynamic responses of the beam. The fluid domain is simulated by using the equations of Navier-Stokes associated with the local ghost-cell immersed boundary method. The results show the method efficiency in dealing with corners and sharp geometries, as beams and airfoils, for fluid-structure problems considering immersed boundaries. Further research efforts will be dedicated to numerical tests for evaluate coupling algorithms, given the methodologies applied.